Efektivitas Pembatasan Penggunaan Gadget terhadap Prestasi Belajar Santri Putri Pondok Al-Istiqomah Tanjungsari Petanahan Kebumen - Ngafifah Ngafifah; Ngarifin Shidiq; Siti Lailiyah (Reflection : Islamic Education Journal, 2026)
This study aims to analyze the impact of restricting gadget use on the learning achievement of female students at Pondok Pesantren Al-Istiqomah Tanjungsari Petanahan Kebumen. The research is motivated by the increasing use of gadgets, which may affect students’ concentration and learning discipline. A qualitative approach with a field research design was employed. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that gadget use restrictions are implemented systematically through rule-setting, supervision, and evaluation. The policy does not prohibit gadget use entirely but regulates it according to time, function, and purpose. The results indicate that the restriction has a positive impact on students’ learning achievement by improving concentration, strengthening time-management discipline, increasing participation in learning activities, and enhancing understanding of learning materials. In addition, a more conducive learning environment is created due to reduced distractions from gadget use. However, the effects are not experienced equally by all students, as some still face challenges related to self-awareness and self-control. Supporting factors include clear regulations, consistent supervision, teacher support, and a conducive boarding school environment, while inhibiting factors include low discipline, peer influence, gadget dependency, limited supervision, and easy access to technology. Overall, gadget use restrictions contribute positively to improving students’ learning achievement.